Bathymetric Highs Control the Along-Strike Variations of the Manila Trench: 2D Numerical Modeling - Ma, Letian; Chen, Lin; Cheng, Zihua; Gerya, Taras; Li, Jiabiao (Frontiers in Earth Science, 2022)
The Manila Trench is located at the eastern boundary of the South China Sea (SCS). It develops through the subduction of the SCS beneath the Philippine Sea Plate (PSP) since the early Neogene, driven by the northwestern plate motion of the PSP. The northern segment of the Manila trench at around 18° N – 21.5° N is characterized by an obvious eastward convex in the trench shape and abrupt changes of slab dip angle, whereas the southern segment of the Manila trench at around 15° N – 18° N is featured by an almost straight NS-trending trench line and smooth subducting slab morphology. However, the cause for the along-strike variations along the Manila trench remains poorly understood. In this study, we employ 2-D thermo-mechanical modeling to investigate how bathymetric highs embedded in the subducting slab affect the topography of overriding plate and the morphology of subducting plate. Three major factors of bathymetric highs are systematically examined: (a) the crustal properties, (b) the width, and (c) the thickness. Geodynamic results suggest that the most important factor controlling abrupt changes in dipping angle is the crustal properties of bathymetric highs. Also, reduction of crustal thickness and increasing the width of continental bathymetric highs favor the abrupt change of dipping angle, whereas thicker (≥ 25 km) bathymetric highs are more likely to be blocked in the subduction zone before slab break-off. According to our numerical modeling results, we suggest that dramatic changes in the dip angle in the northern Manila trench and the convex shape were caused by subduction of a large thin continental terrane, whereas the smooth morphology of subducting slab in the southern segment and straight trench were associated with normal oceanic subduction with small seamounts.